Psychological capital as a personal resource in the JD-R model. Issue 4 (11th May 2018) - Grover, Steven L.; Teo, Stephen T.T.; Pick, David; Roche, Maree; Newton, Cameron J.
Abstract : Purpose: The purpose of this paper is to demystify the role of the personal resource of psychological capital (PsyCap) in the job demands-resources model. The theory suggests that personal resources directly influence perceptions of job demands, job resources, and outcomes. Alternatively, personal resources may moderate the impact of job demands and job resources on outcomes. Design/methodology/approach: A survey of 401 nurses working in the Australian healthcare sector explores the relations among PsyCap, job demands and resources, and psychological well-being and work engagement. Findings: The results suggest that PsyCap directly influences perceptions of job demands and resources and that it directly influences the outcomes of well-being and engagement. Furthermore, job demands and job resources mediate the relation of PsyCap with well-being and engagement, respectively. Research limitations/implications: The moderation effect of PsyCap was not supported, which suggests that PsyCap relates to perceptions as opposed to being a coping mechanism. This finding therefore narrows the scope of personal resources in this important model. Originality/value: The importance of this study lies in its exploration of various ways that personal resources can influence this dominant model and in analyzing the global construct of PsyCap as opposed to some of its constituent parts.